The effect of substances as Volatile oils extracted from Aquatic plants in fighting various diseases - أ. فاطمة الطاهر عبد السلام (Bani Waleed University Journal of Humanities and Applied Sciences, 2024)
Plant extracts have been used for therapeutic purposes for thousands of years. Through experimentation and error, early human populations discovered that some plant extracts had a therapeutic effect, as scientists gradually realized in the early 20th century how to obtain active substances in pure form for use in medicines. Recent reports have indicated that the use of antibiotics as growth catalysts in poultry water and feed has become present in the European Union and poultry producers have been threatened with poultry feeding in the United States of America. (Soltan and colleagues, 2008) due to the survival of some residues of these antibiotics in bird-resolving tissues and damage to human health consuming these meats, herbs and plant extracts have been used to feed poultry as safe and natural materials. So, The case study can be stated in the following question: What is The effect of substances extracted from some plants in fighting various diseases? So, The case study can be stated in the following question: What is The effect of substances extracted from some plants in fighting various diseases? Study Obejectives